Prenatal exposure to consumer product chemical mixtures and size for gestational age at delivery - P. A. Bommarito; B. M. Welch; A. P. Keil; G. P. Baker; D. E. Cantonwine; T. F. McElrath; K. K. Ferguson (BMC, 2021)
Abstract Background While fetal growth is a tightly regulated process, it is sensitive to environmental exposures that occur during pregnancy. Many commonly used consumer products contain chemicals that can disturb processes underlying fetal growth. However, mixtures of these chemicals have been minimally examined. We investigated associations between prenatal exposure to 33 consumer product chemicals (nine organophosphate ester flame retardant [OPE] metabolites, 12 phthalate metabolites, and 12 phenols) and the odds of small- or large-for-gestational age (SGA and LGA) births. Methods This case-control study was comprised of SGA (N = 31), LGA (N = 28), and appropriate for gestational age control (N = 31) births selected from the larger LIFECODES cohort. Biomarkers of exposure to consumer product chemicals were quantified in maternal urine collected from up to three study visits during pregnancy. In a single-pollutant approach, odds ratios (OR) and 95% confidence intervals (CI) of SGA and LGA associated with an interquartile range (IQR)-increase in exposure biomarkers were estimated using multinomial logistic regression. In a multi-pollutant approach, quantile g-computation was used to jointly estimate the OR (95% CI) of SGA and LGA per simultaneous one quartile-change in all biomarkers belonging to each chemical class. Results Among the 33 biomarkers analyzed, 20 were detected in at least 50% of the participants. After adjusting for potential confounders, we observed reduced odds of LGA in association with higher urinary concentrations of several exposure biomarkers. For example, an IQR-increase in the OPE metabolite, diphenyl phosphate, was associated with lower odds of LGA (OR: 0.40 [95% CI: 0.18, 0.87]). Using quantile g-computation, we estimated lower odds of an LGA birth for higher OPE metabolite concentrations (OR: 0.49 [95% CI: 0.27, 0.89]) and phthalate metabolite concentrations (OR: 0.23 [95% CI: 0.07, 0.73]). Associations between consumer product chemicals and SGA were largely null. Conclusions Joint exposure to OPEs and phthalates was associated with lower odds of delivering LGA. Associations with LGA could indicate a specific impact of these exposures on the high end of the birth weight spectrum. Future work to understand this nuance in the associations between consumer product chemical mixtures and fetal growth is warranted.